Achsensymmetrisch?! Praktiken, soziale und sozio-mathematische Normen der Begründung der Achsensymmetrie ebener Figuren in der Grundschule - Häsel-Weide, Uta; Wallner, Melina (Journal für Mathematik-Didaktik)

Uncovering Impact of Innovation: Continuous Stakeholder Engagement through Scenario-based Systems Engineering - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Proceedings of the 21st ISCRAM Conference (ISCRAM 2024))
The importance of extreme weather situations is increasing due to their number and, above all, their impact on stakeholders in emergency response. They are characterized by cascading effects with global and local interdependencies. Extreme data must be included as a basis for decision-making. The impact in emergency response depends on diverse, multidisciplinary competencies required to interpret information. Scenarios are used in various forms of preparation: in exercises, but also for the design of information systems and validation. Based on literature, this article brings together different types of scenarios and related work in the field of Model-Based Systems Engineering. Using an exemplary case relating to possible pluvial urban floods, the added value resulting from a focus on the impact of innovative solutions is discussed. It is shown that the use of scenarios helps to make the desired impact assessable for decision-makers in all phases of research and development projects.

Extending the application of simulation from preparedness to response use cases in weather-induced emergencies - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Mensch und Computer 2024 - Workshopband)
Weather-induced emergencies are characterized by underlying weather phenomena, their evolution in time and space as well as their impact on the environment including people, nature and infrastructure. Typically, simulations are used to consider a variety of potential extreme weather scenarios in preparedness phases. Due to required computing power, duration and high efforts in parameterizing such tools are hardly used within response situations. Enhanced simulation models and surrogate models based on machine learning technologies carry potentials to overcome these challenges. An approach is presented that adopts simulation for the case of flooding events. It considers all phases from demand situation in command posts through advanced parameter space exploration to advanced visualization of simulation results in Augmented Reality. Initial evaluation results are presented, complemented by conclusions on incorporated technologies. The results contribute to future adoption of simulation even in time-critical response situations.
Keywords: extreme weather; emergency response; simulation; Augmented Reality

Kritische Mathematik und die Axiomatik Hilberts - Peckhaus, Volker (Der Geist der kritischen Schule. Kantisches Denken in der Tradition von Jakob Friedrich Fries und Leonard Nelson im 20. Jahrhundert: Wirkungen und Aktualität)

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
The increasing significance of ecological responsibility, stricter political regulations and economic objectives are driving innovation in research fields such as lightweight construction. One of the most important popular methods is the use of multi-material systems. Due to the different geometric and mechanical properties of the various materials used, resource efficient applications and utilizations are possible. Great challenges arise for the joining processes to realize these multi-material systems, since conventional joining processes reach their limits. In the field of mechanical joining processes, there are continuously new approaches, such as superimposing the punch in a self-piercing riveting process with a tumbling kinematic, to increase the number of adaptable process parameters and enhance the process control. Through various preliminary tests, a good understanding of the process has been developed, which allows to directly control the geometric joint parameters by configuring the tumbling strategy. A major challenge, particularly with regard to future industrial applications, is the process time, which is comparatively high due to the tumbling kinematics. In the investigations, a reduction of approximately 90% of the process time is targeted by adapting the joining and tumbling strategy. Therefore, the correlation of the traverse velocity and the tumbling velocity are examined in a gradual series of experiments. To represent realistic applications, the experiments are carried out with a dual-phase steel and a precipitation-hardening aluminum alloy. For identifying the influence of the process parameters on the joining process, a constant rivet–die combination is applied. Further, the examination of force–displacement curves is conducted. Moreover, the determination of geometric joint parameters is reliant upon macrographs to assess the influence of the joining time on the geometric joint formation. The test results show that a significant increase in joining speed with a resulting reduction in process time is feasible. Although the joining properties are affected, reliable joining is possible. In particular, the shaft thickness of the rivet is influenced by the varying proportion of the tumbling process in the joining operation and increases with higher joining speeds.

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
The increasing significance of ecological responsibility, stricter political regulations and economic objectives are driving innovation in research fields such as lightweight construction. One of the most important popular methods is the use of multi-material systems. Due to the different geometric and mechanical properties of the various materials used, resource efficient applications and utilizations are possible. Great challenges arise for the joining processes to realize these multi-material systems, since conventional joining processes reach their limits. In the field of mechanical joining processes, there are continuously new approaches, such as superimposing the punch in a self-piercing riveting process with a tumbling kinematic, to increase the number of adaptable process parameters and enhance the process control. Through various preliminary tests, a good understanding of the process has been developed, which allows to directly control the geometric joint parameters by configuring the tumbling strategy. A major challenge, particularly with regard to future industrial applications, is the process time, which is comparatively high due to the tumbling kinematics. In the investigations, a reduction of approximately 90% of the process time is targeted by adapting the joining and tumbling strategy. Therefore, the correlation of the traverse velocity and the tumbling velocity are examined in a gradual series of experiments. To represent realistic applications, the experiments are carried out with a dual-phase steel and a precipitation-hardening aluminum alloy. For identifying the influence of the process parameters on the joining process, a constant rivet–die combination is applied. Further, the examination of force–displacement curves is conducted. Moreover, the determination of geometric joint parameters is reliant upon macrographs to assess the influence of the joining time on the geometric joint formation. The test results show that a significant increase in joining speed with a resulting reduction in process time is feasible. Although the joining properties are affected, reliable joining is possible. In particular, the shaft thickness of the rivet is influenced by the varying proportion of the tumbling process in the joining operation and increases with higher joining speeds.

Numerical modelling of the influence of viscous fingering on the mechanical properties of structural adhesive joints - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (The 16th International Conference on the Science and Technology of Adhesion and Adhesives)

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)

How Do Attitudes and Self-Efficacy Predict Teachers’Intentions to Use Inclusive Practices? A Cross-National Comparison Between Canada, Germany, Greece, Italy, and Switzerland - Sahli Lozano, Caroline; Wüthrich, Sergej; Kullmann, Harry; Knickenberg, Margarita; Loreman, Tim; Romano, Alessandra; Avramidis, Elias; Woodcock, Stuart; Subban, Pearl (Exceptionality Education International)

Schulisches Wohlbefinden von Schüler*innen der Sekundarstufe I in inklusiven Lerngruppen – Analysen zum Entwicklungsverlauf an der Laborschule Bielefeld - Marker, Rabea; Kullmann, Harry; Zentarra, Dominik; Geist, Sabine; Lütje-Klose, Birgit (Unterrichtswissenschaft)

Schulisches Wohlbefinden von Schüler*innen der Sekundarstufe I in inklusiven Lerngruppen – Analysen zum Entwicklungsverlauf an der Laborschule Bielefeld - Marker, Rabea; Kullmann, Harry; Zentarra, Dominik; Geist, Sabine; Lütje-Klose, Birgit (Unterrichtswissenschaft)

What does the village need to raise a child with additional needs? Thoughts on creating a framework to support collective inclusion - Subban, Pearl; Woodcock, Stuart; Bradford, Brent; Romano, Allesandra; Sahli Lozano, Caroline; Kullmann, Harry; Sharma, Umesh; Loreman, Tim; Avramidis, Elias (Teachers and Teaching)

Lebendiges Silberschmiedehandwerk in Westfalen am Beispiel der 1892 gegründeten Werkstatt Cassau in Paderborn - Harnack, Maria (Graugold. Magazin für Alltagskultur)

Dialectical Jesus - Ficara, Elena (Paradox and Contradiction in Theology)

Hegelian Aristotelianism and the Philosophical Roots of Non-Classical Logics - Ficara, Elena (Aristotle's Organon in Old and New Logic)

Adopting Generative AI for Literature Reviews: An Epistemological Perspective - Schryen, Guido; Marrone, Mauricio; Yang, Jiaqi (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

A Design Theory for Spontaneous Volunteer Coordination Systems in Disaster Response - Betke, Hans; Sperling, Martina; Schryen, Guido; Sackmann, Stefan (Proceedings of the 57th Hawaii International Conference on System Science (HICSS 2024))

Optical bias and cryogenic laser readout of a multipixel superconducting nanowire single photon detector - Thiele, Frederik; Lamberty, Niklas; Hummel, Thomas; Bartley, Tim (APL Photonics)
Cryogenic opto-electronic interconnects are gaining increasing interest as a means to control and readout cryogenic electronic components. The challenge is to achieve sufficient signal integrity with low heat load processing. In this context, we demonstrate the opto-electronic bias and readout of a commercial four-pixel superconducting nanowire single-photon detector array using a cryogenic photodiode and laser. We show that this approach has a similar system detection efficiency to a conventional bias. Furthermore, multi-pixel detection events are faithfully converted between the optical and electrical domains, which allows reliable extraction of amplitude multiplexed photon statistics. Our device has a latent heat load of 2.6 mW, maintains a signal rise time of 3 ns, and operates in free-running (self-resetting) mode at a repetition rate of 600 kHz. This demonstrates the potential of high-bandwidth, low noise, and low heat load opto-electronic interconnects for scalable cryogenic signal processing and transmission.

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024)
Developing Intelligent Technical Systems (ITS) involves a complex process encompassing planning, analysis, design, production, and maintenance. Model-Based Systems Engineering (MBSE) is a key methodology for systematic systems engineering. Designing models for ITS requires harmonious interaction of various elements, posing a challenge in MBSE. Leveraging Generative Artificial Intelligence, we generated a dataset for modeling, using prompt engineering on large language models. The generated artifacts can aid engineers in MBSE design or serve as synthetic training data for AI assistants.
Keywords: Data Driven Design; Design Automation; Systems Engineering (SE); Artificial Intelligence (AI)

Spearhead Data-Driven Model-Based Systems Engineering: Interview Study on Definition, Preconditions, Challenges, Potentials, and Use Cases - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (DS 130: Proceedings of NordDesign 2024, Reykjavik, Iceland, 12th - 14th August 2024)